PEMBINAAN disiplin di lingkungan masyarakat kota Denpasar Made Supartha Endra Kusuma ... [et al.] ; editor, J. Gusti Ketut Gede Arsana - Kusuma, Made Supartha Endra; Arsana, I Gusti Ketut Gede (1995)
xii, 190 hlm ilus 21 cm